A review of derivatives research in accounting and suggestions for future work. Issue 1 (19th February 2019) - Campbell, John L.; Mauler, Landon M.; Pierce, Spencer R.
Abstract : This paper provides a review of research on financial derivatives, with an emphasis on and comprehensive coverage of research published in 15 top accounting journals from 1996 to 2017. We begin with some brief institutional details about derivatives and then summarize studies explaining when and why firms use derivatives. We then discuss the evolution of the accounting rules related to derivatives (and associated disclosure requirements) and studies that examine changes in these requirements over the years. Next, we review the literature that examines the consequences of firms' derivative use to various capital market participants (i.e., managers, analysts, investors, boards of directors, etc.), with an emphasis on the role that the accounting and disclosure rules play in such consequences. Finally, we discuss the importance of industry affiliation on firms' derivative use and the role that industry affiliation plays in derivatives research. Overall, our review suggests that, perhaps due to their inherent complexity and data limitations, derivatives are relatively understudied in accounting, and we highlight several areas where future research is needed.